Microbiological and physics testing encapsulation of Lactobacillus plantarum with kepok banana flour - Legowo, Anang Mohamad; Pramono, Yoyok Budi; Hintono, Antonius; Setiani, Bhakti Etza; Nabila, Aulia Zalfa; Handoko, Nisfa Rama Kamila (International Journal of Advances in Applied Sciences, 2025)
Kepok banana flour (KBF) contains fructo-oligosaccharides (FOS) which can stimulate the growth of Lactobacillus plantarum bacteria in the digestive tract. The encapsulation technique is done to maintain the viability of probiotic bacteria from environmental conditions by packaging using coating materials like skim milk and maltodextrin. This research aims to determine the effect of adding KBF with different concentrations on Lactobacillus plantarum encapsulates. The research design used was a completely randomized design (CRD) with 5 treatments and 4 replications. The treatment given was a concentration of KBF of 0, 2, 4, 6, and 8%. The results obtained were a lactic acid bacteria (LAB) viability value of 8.72 Log CFU/g-9.16 Log CFU/g, a pH value of 6.55-6.43, yield value of 23.39%-23.43%, color of 3.36-3.12, aroma of 2.80-2.88, texture of 3.08-2.92, and overall, 3.12-3.36. The addition of 8% KBF can increase LAB viability, color, and texture, but reduces the pH value, yield, and aroma of Lactobacillus plantarum encapsulates and produces a well-encapsulated microcapsule morphology.